2021
DOI: 10.3390/app11188500
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biosynthesis of Lactones: Gaps and Opportunities towards Sustainable Production

Abstract: Lactones are volatile organic compounds widely present in foods. These chemicals are applied as flavors and fragrances in the food, cosmetics and pharmaceutical industries. Recently, the potential of lactones as green solvents and fuel precursors reinforced their role as platform compounds of future bio-based economies. However, their current mode of production needs to change. Lactones are mainly obtained through chemical synthesis or microbial biotransformation of hydroxy fatty acids. The latter approach is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…After introduction of a hydroxy group, the chain length is reduced by β-oxidation. Under acidic conditions, the shortened hydroxy carboxylic acids finally undergo cyclization to form the lactones [38]. The six coconut-like smelling lactones identified in the current study have been found in cocoa before [9,12,13,29]; however, none of them has been reported as causative for an atypical aroma note in fermented cocoa so far.…”
Section: Odorant Screeningmentioning
confidence: 49%
See 1 more Smart Citation
“…After introduction of a hydroxy group, the chain length is reduced by β-oxidation. Under acidic conditions, the shortened hydroxy carboxylic acids finally undergo cyclization to form the lactones [38]. The six coconut-like smelling lactones identified in the current study have been found in cocoa before [9,12,13,29]; however, none of them has been reported as causative for an atypical aroma note in fermented cocoa so far.…”
Section: Odorant Screeningmentioning
confidence: 49%
“…In both samples, the highest FD factors (2048-4096) were determined for fruity smelling compounds ethyl butanoate (3) and ethyl 2-methylbutanoate (4), bell pepper-like smelling 3-isopropyl-2-methoxypyrazine ( 14), cheesy smelling 2-/3-methylbutanoic acid (23), floral, citrusy smelling geranial (25), rosy smelling 2-phenylethyl acetate (28), cinnamon-like smelling ethyl 3-phenylpropanoate (31), honey-like, rosy smelling 2-phenylethan-1-ol (32), metallic smelling trans-4,5-epoxy-(2E)-dec-2-enal (35), caramel-like smelling 4-hydroxy-2,5-dimethylfuran-3(2H)-one (HDMF; Furaneol ® ) (38), and soup seasoning-like smelling sotolon (43). These compounds are all well-known cocoa odorants and have been reported in numerous studies before [3,9,[29][30][31].…”
Section: Odorant Screeningmentioning
confidence: 99%
“…[8][9][10] g-Lactones are important biologically active molecules and provide building blocks for various fine chemicals (Scheme 1a). [11][12][13][14][15][16] Scheme 1. a) Importance of g-lactones as flavor and fragrance and biologically active compounds. [17][18][19] b) Literature-reported enzymatic conversion of 1,4-keto esters/acids into g-lactones.…”
Section: Introductionmentioning
confidence: 99%
“…gossypii is a pre-WGD member of the Saccharomycetaceae family, more closely related to S. cerevisiae and K. lactis than to other filamentous fungi (Gomes et al, 2014). This fungus is known for its native capacity to overproduce riboflavin (vitamin B 2 ), for which it is industrially exploited for more than 25 years (Aguiar et al, 2015), and also for its ability to de novo biosynthesize other important chemicals such as flavours and fragrances (Birk et al, 2019;Silva et al, 2019aSilva et al, , 2021. In this filamentous fungus, unlike the purine biosynthetic pathway, which is strongly connected with the overproduction of riboflavin (Aguiar et al, 2015), investigation on pyrimidine biosynthesis is limited.…”
Section: Introductionmentioning
confidence: 99%